Differences in healthcare expenditures for inflammatory bowel disease by insurance status, income, and clinical care setting - Park, Michelle; Bhattacharya, Jay; Park, KT (PeerJ PrePrints, 2014)
Background: Socioeconomic factors and insurance status have not been correlated with differential use of healthcare services in inflammatory bowel disease (IBD). Aim: To describe IBD-related expenditures based on insurance and household income with the use of inpatient, outpatient, emergency, and office-based services, and prescribed medications in the United States (US). Methods: We evaluated the Medical Expenditure Panel Survey from 1996 to 2011 of individuals with Crohn’s disease (CD) or ulcerative colitis (UC). Nationally weighted means, proportions, and multivariate regression models examined the relationships between income and insurance status with expenditures. Results: Annual per capita mean expenditures for CD, UC, and all IBD were 10,364 (N=238), 7,827 (N=95), and 9,528, respectively, significantly higher than non-IBD (4,314, N=276,372, p<0.05). Publicly insured patients incurred the highest costs (18,067), over privately insured (8,014, p<0.05) or uninsured patients (5,129, p<0.05). Among all IBD patients, inpatient care composed the highest proportion of costs (3,392, p<0.05). Inpatient costs were disproportionately higher for publicly insured patients. Public insurance had higher odds of total costs than private (OR 2.13, CI 1.08-4.19) or no insurance (OR 4.94, CI 1.26-19.47), with increased odds for inpatient and emergency care. Private insurance had higher costs associated with outpatient care, office-based care, and prescribed medicines. Low-income patients had lower costs associated with outpatient (OR 0.38, CI 0.15-0.95) and office-based care (OR 0.21, CI 0.07-0.62). Conclusions: In the US, high inpatient utilization among publicly insured patients is a previously unrecognized driver of high IBD costs. Bridging this health services gap between SES strata for acute care services may curtail direct IBD-related costs.
Keywords: Crohn’s disease; ulcerative colitis; socioeconomic factors; health insurance